Affine connection adjoined to web W(1, n, 1) - A. A. Duyunova (Научный вестник МГТУ ГА, 2016)
The 3-web and the system of differential equations are adjoined with an associated affine torsion-free connection (the so called canonical connection of an ordinary differential equations’ system). Components of the torsion tensor of this connection are expressed through the functions defining the system of differential equations. A general form of the system of differential equations with the zero torsion tensor is obtained.